Since ll is on the right side of the equation, switch the sides so it is on the left side of the equation.prl+pr2=sprl+pr2=sSince pr2pr2 does not contain the variable to solve for, move it to the right side of the equation by subtracting pr2pr2 from both sides.prl=−pr2+sprl=-pr2+sDivide each term by prpr and simplify.Divide each term in prl=−pr2+sprl=-pr2+s by prpr.prlpr=−pr2pr+sprprlpr=-pr2pr+sprSimplify the left side of the equation by cancelling the common factors.l=−pr2pr+sprl=-pr2pr+sprSimplify each term.
l=−r+spr